FEASIBILITY ANALYSIS OF STATE-OWNED EXPERIMENTAL POND FARMS - Peterson, Richard E; Seo, K K (Indian Journal of Fisheries, 2011)
Creating a frustrating situation of inherent conflict between the long-range objectives of scientists and the short-term needs of commercial growers, the current system in Hawaii of obtaining data from the prawn farmers’ ponds and using the ponds to test management techniques and devices as a return for the subsidy provided in the form of free technical assistance and juveniles for stocking under a three-year period of assistance appears to cause a major bottleneck in industry progress. The authors, taking this into consideration, propose state-owned experimental farm stations for an alternative and provide detailed methods for evaluating their worthwhileness from both the scientists’ and the growers’ points of view.